Implementasi Flashcard Elektronik untuk meningkatkan penguasaan kosa kata siswa - Nashir, Muhammad; Laili, Roudlotun Nurul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2018)
One of the indicators for someone who is mastering a language is having adequate vocabulary. The limited vocabulary causes the difficulty in capturing intentions and ideas while listening, understanding reading text, saying something and uttering thought and idea in mind. The implementation of electronic flashcard was supposed to be able to expand students’ vocabulary due to it excites visual and photographic memory. This classroom action research was performed to increase the seventh grade students’ vocabulary mastery through electronic flashcard at MTs MUKHTAR SYAFAAT – BLOKAGUNG – BANYUWANGI. This research was accomplished in two stages collaborated with an English teacher. The collection data was gained from observation, interview, pre test and post test. The result of this study proved that the application of electronic flashcard media can improve the mastery of students’ vocabulary. It could be seen from enhancement of vocabulary test mean score and the total number of students who got score equal or higher than standard of minimum completeness (KKM) which was 70. The mean score of students’ vocabulary in pretest was 58.24, and then in the first cycle the result of vocabulary mean score was 70.05 and in cycle II it improved to 77.3. The percentage of students who got score least 70 increased from 70.27% in cycle I to 81.08% in cycle II. It showed that the usage of electronic flashcard can extend the achievement of students’ vocabulary.